Diatom based sea surface temperatures in sediment core PS2606-6 - Civel-Mazens, Matthieu; Crosta, Xavier; Cortese, Giuseppe; Lowe, Vikki; Ikehara, Minoru; Itaki, Takuya; Kohfeld, Karen E (In: Civel-Mazens, M et al. (2024): Sediment cores MD19-3575CQ, MD19-3580, COR-1PC, PS2606-6 - subsurface, surface temperature (full resolution and resampled), and DeltaT records [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.973478, 2024)
We present new records in four sediment cores of the Indian sector of the Southern Ocean. Diatom based sea surface temperatures (SST) were predicted using a dataset containing 249 samples as per Crosta et al. (2020) and applying the Modern Analog Technique to relative abundances of 33 diatom taxa.
Keywords: diatoms; Radiolarians; Southern Ocean; temperature reconstruction; transfer function